(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
This scientific article provides a systematic analysis of the main etiological factors, pathophysiological mechanisms, and clinical consequences of hormonal disorders in women of reproductive age. Based on authoritative sources in obstetrics and gynecology, hormonal imbalance is shown to be closely associated with functional and organic alterations in the hypothalamus, pituitary gland, ovaries, thyroid gland, and adrenal glands